Competencias docentes, tecnología y personalidad de los estudiantes del Máster de Secundaria / Teacher competencies, technology and personality among secondary education master’s students - Maria del Sagrario Del-Valle-Díaz; Javier Rodriguez-Torres; José Jesús Castro-Sánchez; Gerardo Fernández-Escribano (Revista Latinoamericana de Tecnología Educativa)
This study, carried out for predictive and diagnostic purposes, analyses the acquisition of teacher competencies and the integration of technology in learning, as related to personality, among students on the Master’s in Secondary Education at the University of Castilla-La Mancha (Spain). Methodology: 241 students (105 men and 136 women) from the 2019–2020 cohort took part. To evaluate the self-efficacy of teacher competencies, the scale of six competencies was used, taking into account the context of practice. To assess the impact of technology on learning, the bifactorial scale of learning and learning strategies was used, and the BFI-10 questionnaire was used to assess personality traits. A correlation analysis was carried out, 12 mediation models were calculated, and a bootstrap analysis was conducted to calculate the indirect effects of the mediations. The results show that the acquisition of all teacher competencies is significantly and positively correlated with technology learning, particularly subject knowledge, and methodological competence, where the traits of conscientiousness and openness are significant. Of the 12 mediation models, the model that showed partial mediation was competence for collaboration with tutors, predicted by technology learning, mediated by conscientiousness. The findings show an understanding of how to steer university training in the context of the current education system.